2003
DOI: 10.1037/0033-295x.110.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Recasting (the near-miss to) Weber's law.

Abstract: The authors argue mathematically that a common, power-function model of the just-noticeable difference in stimulus intensities is logically inconsistent with an exponent other than 1 in those frequent situations in which a particular averaging over experimental conditions has taken place. The authors show that an alternative power-law model, one which does not share this logical inconsistency, provides a good fit to many well-known, psychoacoustic intensity discrimination data. They also show that the exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 40 publications
1
31
1
Order By: Relevance
“…(16) in particular) is a very strong and useful constraint. For example, the model xðxÞ ¼ x þ kx b is incompatible with the group property (16); see Falmagne (1985) and Doble, Falmagne, and Berg (2003) for a detailed discussion of this fact.…”
Section: Transforming Empirical Datamentioning
confidence: 97%
“…(16) in particular) is a very strong and useful constraint. For example, the model xðxÞ ¼ x þ kx b is incompatible with the group property (16); see Falmagne (1985) and Doble, Falmagne, and Berg (2003) for a detailed discussion of this fact.…”
Section: Transforming Empirical Datamentioning
confidence: 97%
“…2AFC) constrain the possible relationships between and € ΔI JND . A recent discussion of these constraints can be found in Doble, Falmagne, and Berg (2003) and Iverson (2006aIverson ( , 2006b). All are satisfied by Weber's Law.…”
Section: Weber's Lawmentioning
confidence: 99%
“…A similar assumption has been proposed by Falmagne and his colleagues in the study of discriminability (Doble et al, 2003;Falmagne, 1994). The relevant experimental work on the intensity discrimination of pure tones was recently reported by Doble, Falmagne, and Berg (2004), where they clearly showed that the exponent in the homogeneity equation is not a constant but a function of the discrimination criterion.…”
Section: Empirical Evidencementioning
confidence: 70%
“…Accordingly, a more general formulation, which states that D p is homogeneous of degree r (r40), has been proposed, to which the name ''nearmiss to Weber's law'' is attached (for more discussion, see Doble et al, 2003;Falmagne, 1985Falmagne, , 1994.…”
Section: The Near-miss To Weber's Law For Rtsmentioning
confidence: 99%
See 1 more Smart Citation